2021
DOI: 10.1136/jim-2020-001613
|View full text |Cite
|
Sign up to set email alerts
|

Remitting Seronegative Symmetrical Synovitis with Pitting Edema: A Review

Abstract: Remitting seronegative symmetrical synovitis with pitting edema (RS3PE) is a rare benign rheumatological condition characterized by sudden-onset symmetrical distal extremity edema. It can present as an isolated disease process or could be associated with other conditions. Rheumatoid factor and anticitrullinated protein antibodies are negative by definition. In current literature, there is paucity of data about the disease process. We performed a literature search using the PubMed database to identify 38 articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Poor response to low-dose prednisolone is associated with malignancies in RS 3 PE in our study, and some reported cases of paraneoplastic RS 3 PE are also revealed poor response to glucocorticoid [ 2 , 18 ]. However, rapid response to glucocorticoid therapy is also found for some paraneoplastic RS 3 PE, and there are no clinical variables for predicting malignancy in RS 3 PE [ 1 , 3 , 4 , 19 ], which calls for more effective biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Poor response to low-dose prednisolone is associated with malignancies in RS 3 PE in our study, and some reported cases of paraneoplastic RS 3 PE are also revealed poor response to glucocorticoid [ 2 , 18 ]. However, rapid response to glucocorticoid therapy is also found for some paraneoplastic RS 3 PE, and there are no clinical variables for predicting malignancy in RS 3 PE [ 1 , 3 , 4 , 19 ], which calls for more effective biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Poor response to low-dose prednisolone is associated with malignancies in RS 3 PE in our study, and some reported cases of paraneoplastic RS 3 PE are also revealed poor response to glucocorticoid [2,18] . However, rapid response to glucocorticoid therapy is also found for some paraneoplastic RS 3 PE, and there are no clinical variables for predicting malignancy in RS 3 PE [1,3,4,19] , which calls for more effective biomarkers. Interestingly, our study discovered bFGF is the only angiogenesis cytokine which is elevated particularly in RS 3 PE associated malignancy, and further multiple logistic regressions revealed elevation of bFGF may serve as a marker for predicting malignancy in RS 3 PE.…”
Section: Discussionmentioning
confidence: 99%
“…Remitting seronegative symmetrical synovitis with pitting edema (RS3PE) is a rare condition with underlying polyarthritis, pitting edema, and negative rheumatoid factor [1][2][3][4]. It can be associated with an underlying rheumatological condition or can present as a paraneoplastic syndrome with malignancy [4].…”
Section: Introductionmentioning
confidence: 99%